2020
DOI: 10.3389/fpsyg.2020.602401
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Cranial Volume as a Sensitive Marker of Parental Investment: The Role of Non-material Resources?

Abstract: Growth of different body parts in humans is sensitive to different resource constraints that are mediated by parental investment. Parental investment can involve the expenditure of material, cognitive, and emotional resources on offspring. Cranial volume, an important predictor of cognitive ability, appears understudied in this context. We asked (1) whether there are associations between growth and family structure, self-reported estimates for resource availability, and sibling number; and (2) whether these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…For instance, meat intake from 4-to 12-mo-olds and 4-to 16-mo-olds was positively and significantly related to psychomotor developmental indices (Morgan et al, 2004). A cross sectional study among 672 children that measured cranial volume (Lauringson et al, 2020), a proxy of cognitive development (Nave et al, 2019;Valge et al, 2019), reported a negative correlation between meat shortage in childhood and cranial size in adolescents. A longitudinal study on rural children in Nepal by Miller et al (2016) indicated that 43% of the variation in cranial circumference was explained by weight for age scores and consumption of meats, with those consuming more meats having greater cranial circumference scores.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, meat intake from 4-to 12-mo-olds and 4-to 16-mo-olds was positively and significantly related to psychomotor developmental indices (Morgan et al, 2004). A cross sectional study among 672 children that measured cranial volume (Lauringson et al, 2020), a proxy of cognitive development (Nave et al, 2019;Valge et al, 2019), reported a negative correlation between meat shortage in childhood and cranial size in adolescents. A longitudinal study on rural children in Nepal by Miller et al (2016) indicated that 43% of the variation in cranial circumference was explained by weight for age scores and consumption of meats, with those consuming more meats having greater cranial circumference scores.…”
Section: Discussionmentioning
confidence: 99%
“…Stressful life events and limited resource availability contribute to impaired health and immune function in children and adolescents (Dunkel et al, 2020;Kim et al, 2020;Schmeer et al, 2019;Wickrama et al, 2005;Yiğit et al, 2018). For example, children born in socioeconomically disadvantaged families had higher probabilities to have developmental impairments due to the inability to provide proper nutrition, vaccination, and adequate access to health care (Krams et al, 2019;Lauringson et al, 2020;Rubika et al, 2020). Likewise, children from unstable family environments are more likely to develop fast LH strategies which can contribute to the development of higher psychopathological symptoms (Hurst & Kavanagh, 2017;Kahl et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Organisms have limited amounts of time, energy, and resources at their disposal, that need to be allocated among competing demands. This leads to well-documented tradeoffs between different life history domains, most notably investing in survival (i.e., growth, self-maintenance, and immunity) or reproduction (i.e., short-term mating and competition vs. long-term mating and parenting) ( Krams et al, 2019 ; Luoto et al, 2019 ; Laskowski et al, 2020 ; Lauringson et al, 2020 ; Rubika et al, 2020 ).…”
Section: Sexual Selection For Eveningness and Fast Life History Stratmentioning
confidence: 99%